Maleficent (2014) and Attachment Theory: Understanding the Emotional Depths of Villainy - Fara Dhiba; Dinda Rachma Juwita (English Language Education, Universitas Internasional Batam, 2024)
The purposes of the analysis are to discuss the revenge and love of the main character in Maleficent movie through attachment theory. The method used for this analysis is qualitative method. The theory for this analysis is used from attachment theory, initially introduced by John Bowlby and Mary Ainsworth, serves as a widely accepted explanation for the development of affectional bonds between individuals (Bowlby, 1983). The data for this analysis are taking by watching the movie and analysis the dialogue from the movie that related. This analysis examines revenge and love in Maleficent using attachment theory. A qualitative method analyzes key dialogues to explore emotional bonds.This the result concludes the film with a message about the power of love, revenge that can transcend differences.